Mechanisms of Action, Resistance, Toxicity, and Recent Developments of Cisplatin as Anticancer Agent: A Comprehensive Review - Lisdawati Pabisa; Ahyar Ahmad; Harnaningsih Karim (Jurnal Kimia Sains dan Aplikasi, 2026)
Cisplatin is among the most potent chemotherapy agents used to treat a range of cancers, including those affecting the ovaries, testes, lungs, and bladder. Its primary mode of operation involves creating cross-links in DNA, which blocks cell division and gene expression, ultimately leading to programmed cell death. Unfortunately, its therapeutic benefits are frequently undermined by harmful side effects and the development of resistance in cancer cells. This research seeks to delve deeply into cisplatin’s mechanisms, covering how it enters cells, gets activated internally, and interacts with DNA and key proteins. Additionally, it explores advancements in nanoparticle-based cisplatin delivery systems and platinum (Pt[IV]) compounds designed to enhance systemic absorption and reduce overall toxicity. Drawing on a review of 166 studies across five key databases, modifications to drug-delivery methods have shown notable improvements in cisplatin’s performance across different cancer types. As a result, innovative formulations and tactics to tackle resistance could broaden cisplatin’s role as a more targeted and safer cancer-fighting drug. This review was conducted using a structured literature search without a formal risk-of-bias assessment.